Frequency of drug resistance in Plasmodium falciparum: a nonsynergistic combination of 5-fluoroorotate and atovaquone suppresses in vitro resistance. - Gassis, S (1996)
A combination of 5-fluoroorotate and atovaquone eliminated Plasmodium falciparum in long-term cultures more efficiently than either compound alone. The improved potency came not through synergistic activity but through decreased frequency of drug resistance. In support of this finding, it was shown that 5-fluoroorotate and atovaquone do not act in a synergistic fashion, that 5-fluoroorotate-resistant and atovaquone-resistant P. falciparum organisms generated in vitro do not show cross-resistance, and that the frequency of simultaneous resistance to the two compounds approached the product of their individual resistance frequencies. To demonstrate the last finding, and establish proof of principle, an in vitro method was developed for measuring the frequency of drug resistance in P. falciparum. By this method, it was shown that the frequency of resistance to 10(-7) M 5-fluoroorotate was about 10(-6) and the frequency of resistance to 10(-8) M atovaquone was about 10(-5); the frequency of simultaneous resistance to a combination of 10(-7) M 5-fluoroorotate and 10(-8) M atovaquone was less than 5 x 10(-10). On the basis of additional measurements, it was estimated that the frequency of simultaneous resistance to higher, pharmacologically more relevant, concentrations of 10(-6) M 5-fluoroorotate and 10(-7) M atovaquone would be less than 10(-17). Control experiments demonstrated that these drug combinations did not cause increased toxicity to mammalian cells in culture. On this basis, it is predicted that a combination of 5-fluoroorotate and atovaquone will successfully eliminate typical malarial infections in animals and in human patients at doses that are readily tolerated.